CHALLENGES IN ASSESSING CHARACTER EDUCATION IN ELT: IMPLICATIONS FROM A CASE STUDY IN A CHRISTIAN UNIVERSITY - Mambu, Joseph Ernest (TEFLIN Journal, 2015)
In this article I examine some challenges of assessing character education in the context of Teaching English as a Foreign Language in Indonesia (TEFLIN). Major sources of character education in Indonesia (e.g., Kurikulum 2013) seem to be religious values. However, there are two salient problems. First, in religiously inspired character education, there are concerns about religious values imposition. Second, it is oftentimes vague what types of, and how, character education can be evaluated in English language teaching and learning settings. In the context of an EFL teacher education program in a Christian university that I studied, one Christian student showed her religious dogmatism in classroom interactions or elsewhere in which peers having different religious views were present. Students' communicative competence in expressing religious values can be assessed by examining their growing self-reflexivity (which problematizes dogmatism), among others, in their discourse. Character education assessment rubrics are developed from the cases reported here, in light of: (1) the Indonesian government's guidelines for assessing character education; (2) critical ELT; and (3) Celce-Murcia's (2007) model of communicative competence.